Role of Nutrients and Foods in Attenuation of Cardiac Remodeling through Oxidative Stress Pathways - Lazzarin, Taline [UNESP]; Garcia, Leonardo Rufino [UNESP]; Martins, Danilo [UNESP]; Queiroz, Diego Aparecido Rios [UNESP]; Tonon, Carolina Rodrigues [UNESP]; Balin, Paola da Silva [UNESP]; Polegato, Bertha Furlan [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Azevedo, Paula Schmidt [UNESP]; Minicucci, Marcos [UNESP]; Zornoff, Leonardo [UNESP] (MDPI, 2022)
Cardiac remodeling is defined as a group of molecular, cellular, and interstitial changes that manifest clinically as changes in the heart’s size, mass, geometry, and function after different injuries. Importantly, remodeling is associated with increased risk of ventricular dysfunction and heart failure. Therefore, strategies to attenuate this process are critical. Reactive oxygen species and oxidative stress play critical roles in remodeling. Importantly, antioxidative dietary compounds potentially have protective properties against remodeling. Therefore, this review evaluates the role of nutrients and food as modulators of cardiac remodeling.
Keywords: antioxidants; cardiac remodeling; food; heart failure